MEASUREMENT OF CUSTOMER SATISFACTION AT CAREER CENTRE IN HIGHER EDUCATION INSTITUTION - Harry Widyantoro (Journal of Economics, Business, and Accountancy Ventura, 2012)
The role of career center in a higher education institution (HEI) is vital as it is aimed at helpingthe graduates adapt to work when they get a job. Besides that, it is also a key to determinethe success of the education process. This research attempts to investigate the students’satisfaction on the pre-job services provided by the career center in preparing them withknowledge and skills to get a job through the following programs namely job preparationcourses, job fairs, and a hiring program. The research is qualitative and the data were gatheredfrom a tracer study. It showed that the students were satisfied with the ease to obtain thepre-job services provided in campus and the availability of vacancy board regularly informingvacancies needed by companies. However, the students were not satisfied with the serviceprovided by the career centre staff. As such, it is now recommended that the career centerstaff’s skills must be improved by briefing them with soft skills and making them updated withinformation on career center programs and the vacancies, since from the students’ point ofview, the unit service performance was also considered the institution’s performance as awhole.